VALUASI EKONOMI SUMBERDAYA ALAM RAWA PENING DAN STRATEGI PELESTARIANYA DI KABUPATEN SEMARANG - Gerhard, Gerhard; Susilowati, Indah (Diponegoro Journal of Economics, 2013)
Rawa Pening swamp like is a natural resource which is located in Semarang district, also has a strategic role in various fields. The purpose from this research to answer the problems that occur in the preservation of Rawa Pening. The problem is; (1) Rawa Pening swamp like Lax management by communities,Â governments, the private sector and academia, (2) the decrease in resource capacity Rawa Pening swamp like, Rawa Pening resulting Rawa stop providing benefits, and (3) the lack of community participation, in maintaining and preserving the Rawa Pening swamp like. So that appropriate strategies are needed to preserve the Swamp. The method of analysis used; cost - benefit ratio, co-mangement and analysis hierarchy process.Valuations of Rawa Pening swamp like is Rp16.291.392.000. Covering costs; stocking fish grascap, pengakatan peat, floating islands and outreach. Costs are calculated based on interviews with leading agents and surveys, BC ratio is 1.2.Prospects and community participation is considered good enough, of the 50 respondents can be described with the already good value in every indicator co-mangement. Although still in its feel some lack of communication between each - each stakeholder.Rawa Pening swamp like preservation strategies can be started with cleaning water hyacinth, reduce waste pollution (eutrophication), developing into the Rawa Pening swamp like as attractionsÂ nature tourism, and organsasi established within the government's control.